Osteosarcoma cells relate functionally with stromal cells favoring a lung niche permissive for the establishment of metastatic tumor cells - Valenzuela Alvarez, Matias Juan Pablo (2023)
Osteosarcoma (OS) is the most common bone tumor and 20% of the patients are diagnosed with metastatic OS at first diagnosis. Undetectable metastases at the time of diagnosis are also a major complication. MSCs display abilities that enable tumor growth. We demonstrated that in vitro, MSCs migrated more towards the secretome of non-metastatic OS cells. When challenged to a secretome from lungs pre-loaded with OS cells, MSCs migrated more towards lungs colonized with metastatic OS cells. Furthermore, MSCs had a preferential migratory and homing behavior in vivo towards lungs´ colonized by metastatic OS cells. In addition, metastatic OS cells showed a higher migratory response towards the MSCs secretome. This feature partnered with increased CTSD expression and release of active MMP2 by metastatic OS cells. We assessed two complementary tumor capabilities relevant to metastatic spread, highlighting the importance of inherent cell features, but also underlining the importance of signaling integration across the niche, suggesting that an interplay of migratory responses between already established OS cells in the lungs, prometastatic OS cells in the primary tumor, and circulating MSCs. Pulmonary metastases remain as a major determinant of OS mortality, and identification of mechanisms and differentially expressed genes would help identify markers and targets for therapeutic approaches of metastatic spread.